PENGARUH DENDA TERHADAP TINGKAT NON PERFORMING LOAN (STUDI KASUS PADA PT. BRI (PERSERO),Tbk CABANG KEDIRI TAHUN 2012-2014) - Sherly Ayu Aprylya (Jurnal Akuntansi dan Ekonomi Bisnis PSDKU kediri, 2016)
This research aims to know the influence of fines against the level of NPL. Fines in this study was divided into two fine daily and monthly fines as measured by nominal. NPL at this research is measured by a ratio. This research is the research hypothesis tests that test the influence of the variables that can affect the level of NPL. This study uses secondary data collection techniques, by conducting studies, librarianship and documentation. Secondary data used in the study was obtained from the financial statements of PT BRI (Persero), Tbk branch of Kediri in 2012-2014. The sample in this research is one hundred clients with credit research period from 2012 to 2014, with a sampling technique used was purposive sampling. Technique of data analysis in this study using multiple linear regression, hypothesis testing method used is test the coefficient of determination , the keberartian test model, and the significance of the individual parameters. Determination of coefficient of test results was 33.5%, which means that daily fines and fines affecting monthly NPL amounting to 33.5% and the rest IE 66,5% explained by causes other than the independent variable used in this research. The results of this research show that simultaneously daily fines and fines significantly influential monthly against the level of NPL. The influential daily fines partially significantly to the level of NPL, and significantly influential monthly fines against the level of NPL.